Inclusive Revolution: Children’s Right to Participation and Inclusivity in Child-Friendly Schools in Indonesia - Muhammad Fajhriyadi Hastira; Aliyah Ahmad; Mustika Syaharuddin; Ali Maksum (Badan Kebijakan Pendidikan Dasar dan Menengah, Kemendikdasmen, 2025)
This study aims to examine the implementation of child participation and inclusivity values within Child-Friendly School (CFS) program in Indonesia employing a hexahelix approach to highlight the gap between policy and practice. The CFS strategy is a national initiative to realize inclusive and participatory education in Indonesia, based on children’s rights and Sustainable Development Goals. This study applied a qualitative descriptive method through analysis of regulatory documents, guidelines, scientific literature, and collaborative data related to CFS implementation. Vygotsky’s theoretical framework on social constructivism and Bronfenbrenner’s ecological theory of child development were used to interpret the dynamics of CFS implementation. The findings indicate the difference in implementation across institutions, particularly in the aspects of child involvement and cross-sector coordination. The hexahelix approach strengthens the effectiveness of CFS through multi-stakeholder collaboration. The study recommends establishing a hexahelix collaboration forum at the local level and developing training programs for educators to optimize CFS principles. This study contributes to the academic gap in understanding and improving the implementation of CFS in Indonesia.